Disposable electrochemical sensors for healthcare monitoring : material properties and design - Pandikumar, A.; Devi, K. S. Shalini (RSC detection science series, 2021)
The book focusses on the emerging disposable electrochemical sensors in the health sector and advancement of analytical devices to monitor diabetic, cancer and cardiovascular patients using different nanomaterials.